Chlamydia Trachomatis Tonsillopharyngitis - Özmen Öztürk; Hüseyin Seven (Case Reports in Otolaryngology)
Reports about the extragenital spread of Chlamydia trachomatis (CT) to oropharynx are limited. We report a male patient with progressive tonsillopharyngitis resistant to amoxicillin/clavulanic acid therapy. The patient presented 9 days after an orogenital and oroanal sexual intercourse with a female sex worker. The microimmunofluorescence revealed CT tonsillopharyngitis, and after completing a one-week course of doxycycline, the patient recovered completely. More cases of CT tonsillopharyngitis may be revealed if attention is paid to an association of sexual activity with enduring tonsillopharyngitis.